Professional nurses' perceptions regarding clinical competence of community service nurses in North West province, South Africa - Kholofelo L. Matlhaba; Abel J. Pienaar; Leepile A. Sehularo (AOSIS, 2021)
Background: South African Nursing Council requires nurses who successfully complete their training to perform a year of community service before obtaining registration as professional nurses (Regulation 425). Community service for health professionals was introduced as a strategy to retain newly qualified professionals within the country. The premise is that community service for newly graduated nurses gives them the opportunity to develop skills and acquire knowledge critical in their professional development. Aim: To explore and describe the perceptions of professional nurses as the supervisors of community service nurses (CSNs) during their 12 months of community service. Setting: Selected hospitals of the North West province, South Africa. Methods: A qualitative, exploratory and descriptive design was used. The study was conducted between September and November 2018 at three public hospitals in the North West province. Through purposive sampling, 15 professional nurses who supervise CSNs participated in the study. Data were collected in three focus group discussions using semi-structured questions. All focus group discussions were recorded and transcribed for analysis. Data were analysed using Pienaar's four steps of thematic analysis. Results: Three themes emerged: perceptions of clinical competence, challenges impacting clinical competence and suggestions to improve clinical competence. Conclusion: It is suggested that even though the majority of CSNs were perceived to be competent and capable of working independently, they still required supervision and mentorship to refine their competency. Furthermore, the study reported similar challenges noted from previous studies that were perceived to be affecting CSNs' ability to deliver quality health care, and therefore recommendations for improvement were made. Contribution: The study contributed to the developed the clinical competence evaluation tool which will be of benefit to the future community service nurses in the province.